Chemical Quality of Surface Water of Bhola Sadar Upazila in Bangladesh for Irrigation, Aquaculture, Drinking and Livestock Consumption (Journal of Environmental Science and Natural Resources, 2015)
A study was carried out with 25 pond water samples of Bhola Sadar Upazila to assess the quality of surface water for irrigation, aquaculture, drinking and livestock consumption. Chemical analyses of different parameters were done to assess the quality of water. All of the water samples showed slightly acidic in nature. Sixteen surface water samples were not suitable for drinking and aquaculture in respect of pH (pH 5.0 mg L-1) K content. Six samples were unsuitable for livestock due to higher (Cl >30mgL- 1) Cl values. SSP rated 9 samples as good, 1 as excellent, 6 as doubtful and 9 as permissible for irrigation. With respect to RSC 21 samples were suitable, 3 were marginal and 1 was unsuitable for irrigation. Hardness classified 14 samples within moderately hard, 10 within soft and only one as hard limit for irrigation and 1 sample (No. 16) was unsuitable for livestock consumption. P, B, Cu and As concentration categorized all the samples suitable for irrigation, aquaculture, drinking and livestock consumption.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22053 J. Environ. Sci. & Natural Resources, 6(1): 131-140 2013